METTL3-Mediated N6-Methyladenosine Modification Is Involved in the Dysregulation of NRIP1 Expression in Down Syndrome - Shi, Weili; Yang, Fan; Dai, Ranran; Sun, Yafei; Chu, Yan; Liao, Shixiu; Hao, Bingtao (Frontiers in Cell and Developmental Biology, 2021)
Down syndrome (DS) is a common genetic condition in which a person is born with an extra copy of chromosome 21. Intellectual disability is the most common characteristic of Down syndrome. N6-methyladenosine (m6A) is a common RNA modification that is implicated in many biological processes. It is highly enriched within the brain and plays an essential role in human brain development. However, the mRNA m6A modification in the fetal brain of Down syndrome has not been explored. Here, we report N6-methyladenosine (m6A) mRNA profiles and mRNA expression profiles of fetal brain cortex tissue from DSs and controls. The nuclear receptor interacting protein 1 (NRIP1/RIP140) is coded by a highly conserved chromosome 21 (Hsa21) gene. Overexpression of NRIP1 is associated with mitochondrial dysfunction in Down syndrome. We observed significant changes of NRIP1 in both the m6A level and the RNA level. The increased expression of NRIP1 in DS fetal brains was confirmed by qPCR and Western blot. m6A modification of the NRIP1 mRNA decreased in the DS fetal cortex. METTL3 knockdown reduced the m6A modification of NRIP1 mRNA and increased its expression, and an increase in NRIP1 m6A modification and a decrease in its expression were observed in METTL3-overexpressed cells. The Luciferase reporter assay confirmed that METTL3 regulates NRIP1 expression in an m6A-dependent manner. The decay rate of NRIP1 mRNA was significantly reduced in METTL3-knockdown cells, but increased in METTL3-overexpressed cells. We proposed that the m6A modification of NRIP1 mRNA in DS fetal brain tissue is reduced, reducing its transcript degradation rate, resulting in abnormally increased expression of NRIP1 in the DS brain. It provides a new mechanism for the molecular pathology of DS and leads to a new insight that may become therapeutically relevant.